2011
DOI: 10.1016/j.aenj.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient privacy and confidentiality in one regional Emergency Department – A quality project

Abstract: Background Patient privacy and confidentiality (PPaC) is an important consideration for nurses and other members of the health care team. Can a patient expect to have confidentiality and in particular privacy in the current climate of emergency health care? Do staff who work in the Emergency Department (ED) see confidentiality as an important factor when providing emergency care? These questions are important to consider. Methods This is a two phased quality improvement project, developed and implemented over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…The design of nursing units could affect patients' physical privacy (Lu, Cai, & Bosch, 2016). Research has shown that solid walls (Calleja & Forrest, 2011), partitions at registration, and team rooms in pods are beneficial for improving privacy (Zamani, 2019). Understanding the balance between visibility and perception of privacy is an important issue (Fay, Cai, & Real, 2019).…”
Section: Visibility Affects Communication and Privacymentioning
confidence: 99%
“…The design of nursing units could affect patients' physical privacy (Lu, Cai, & Bosch, 2016). Research has shown that solid walls (Calleja & Forrest, 2011), partitions at registration, and team rooms in pods are beneficial for improving privacy (Zamani, 2019). Understanding the balance between visibility and perception of privacy is an important issue (Fay, Cai, & Real, 2019).…”
Section: Visibility Affects Communication and Privacymentioning
confidence: 99%
“…Privacy and confidentiality are critically important components of patient care [1, 2]. Healthcare professionals are ethically obliged to protect patient confidentiality and ensure discretion [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…(2016) the healthcare professionals' poor handling of patient records is due to lack of knowledge, and in many cases, the breaches of privacy are unintentional. Overall, the healthcare professionals' low awareness and knowledge concerning the protection of confidentiality has been recognised previously (Ayatollahi et al., 2009; Calleja & Forrest, 2011). More education concerning patients' rights has been suggested for all healthcare workers, students in the field and patients and their significant others in order to enhance the realisation of patient's privacy.…”
Section: Discussionmentioning
confidence: 89%
“…However, according to Beltran-Aroca et al (2016) the healthcare professionals' poor handling of patient records is due to lack of knowledge, and in many cases, the breaches of privacy are unintentional. Overall, the healthcare professionals' low awareness and knowledge concerning the protection of confidentiality has been recognised previously (Ayatollahi et al, 2009;Calleja & Forrest, 2011). More education concerning TA B L E 3 Results for research questions: (a) How is informational privacy described in the field of prehospital emergency care, (b) How is the patient's informational privacy realised in prehospital emergency care and (c) What are the factors related to the realisation of patient's informational privacy in prehospital emergency care?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation